A method for producing a metal-coated quartz optical fiber
Patent Information
- Application Number
- CN202410506407.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-25
AI Technical Summary
[0005]由于金属与石英玻璃属于异种材料,在机械强度、弹性模量、线性热膨胀等物理性能方面差别较大,现有的金属与玻璃连接工艺如钎焊、扩散连接、激光焊、离子注入与沉积、阳极键合等无法直接用于光纤金属化上
[0021]本发明提供了一种金属涂层石英光纤的制备方法,先制备合适尺寸的疏松多孔二氧化硅圆柱套筒中间体,经过一系列工艺处理后,通过在石英光纤上先沉积100微米以下的金属薄膜,再用电镀技术使薄膜增厚,得到金属涂层石英光纤。本发明可使制备得到的石英光纤表面与涂覆层的结合强度高且光纤本体的力学性能不受破坏。
Smart Images

Figure CN118420215B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of quartz optical fiber technology, and specifically relates to a method for preparing a metal-coated quartz optical fiber. Background Technology
[0002] Quartz optical fiber generally consists of a core, cladding, and coating. Coating the outside of the fiber cladding can prevent stress concentration, avoid increased loss, and effectively protect the fiber, making it suitable for different environments. This is of great significance for improving the overall performance of optical fiber and expanding its application fields.
[0003] Currently, the mainstream optical fiber coating material internationally is acrylic coating. The advantages of this coating include rapid curing, ease of production, easy peeling, and low cost. Its disadvantage is poor high-temperature resistance; its operating temperature range is generally -60-85℃, which cannot meet the increasing demands of applications in extreme environments such as high temperatures and radiation. High-temperature resistant coatings mainly include polyimide coatings, carbon coatings, and metal coatings. Polyimide-coated optical fibers exhibit excellent thermal stability at normal high temperatures, possessing both radiation resistance and good dielectric properties, and can be used for extended periods below 300℃. When the instantaneous temperature exceeds 400℃, the polyimide coating may carbonize. Carbon-coated optical fibers have excellent sealing properties, with a thickness of only a few angstroms, blocking hydrogen and water vapor. To prevent fiber damage, a secondary coating is usually required outside the carbon layer, using standard UV-curable acrylic or thermosetting polyimide polymer coatings as a protective layer. Therefore, its operating conditions are similar to those of polymer coatings.
[0004] Metal-coated optical fibers are optical fibers with protective layers of metals such as Al, Cu, and Au coated on their surface. These fibers can be used in harsh environments such as high temperatures, vacuum, and nuclear radiation. Metal coatings effectively protect the fiber surface from water vapor corrosion, reduce static fatigue effects, and improve the fiber's mechanical reliability. They also prevent hydrogen from permeating into the fiber core, maintaining high optical transmittance in hydrogen-containing environments. For example, Al-coated optical fibers can operate at temperatures up to 400°C and can function stably for extended periods under high stress and large bending conditions. Au-coated optical fibers can operate at temperatures up to 700°C, exhibit excellent corrosion resistance, and can be used in many harsh environments such as gas turbine temperature / strain monitoring, oil and gas well downhole sensing, and high vacuum or high pressure applications.
[0005] Because metals and quartz glass are dissimilar materials, they differ significantly in physical properties such as mechanical strength, elastic modulus, and linear thermal expansion. Existing metal-glass bonding processes, such as brazing, diffusion bonding, laser welding, ion implantation and deposition, and anodic bonding, cannot be directly applied to optical fiber metallization. Currently, the metal coating layer on the surface of commercial quartz optical fibers mainly adopts online fusion coating, which not only requires expensive equipment but also results in a metal layer thickness of only tens of micrometers, severely limiting the application of metal-coated optical fibers. Furthermore, offline methods for metallizing quartz optical fibers, such as vacuum evaporation, sputtering, electroplating, and chemical plating, also have limitations. In particular, the relatively low bonding strength between the metal coating and the fiber substrate, and the damage to the fiber substrate during the roughening process of chemical plating or electroplating, affect its optical transmission characteristics and mechanical properties, reducing its service life. These issues urgently need improvement. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing metal-coated quartz optical fibers.
[0007] A method for preparing a metal-coated quartz optical fiber includes the following steps:
[0008] Step 1: Prepare a loose and porous silica cylindrical sleeve intermediate of appropriate size, and prepare a quartz glass cylindrical sleeve with nickel oxide micro and nano particles embedded on the surface.
[0009] Step 2: Insert the optical fiber preform into a quartz glass cylindrical sleeve with nickel oxide micro-nano particles embedded on its surface, assemble them into a kit, and draw them into the required optical fiber on the drawing tower;
[0010] Step 3: Under a hydrogen atmosphere, the drawn optical fiber is subjected to a reduction treatment to reduce the nickel oxide micro-nano particles on the surface to metallic nickel; then, a thin metal coating is deposited on the surface of the optical fiber, and then thickened by electroplating to obtain a quartz optical fiber with a certain thickness of metal coating on the surface.
[0011] Further, the preparation method of the loose porous silica cylindrical sleeve intermediate in step 1 is as follows: 40-50 parts of amorphous nano-quartz glass powder, 30-40 parts of 2-hydroxyethyl methacrylate as a photopolymerization monomer, 16-20 parts of 2-phenoxyethanol as a diluent, 5-10 parts of tetra(ethylene glycol) diacrylate as a crosslinking agent, 0.5-1 part of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as a photosensitizer, and 0.1-0.5 parts of hydroquinone as a light absorber are mixed evenly; the evenly mixed material is placed in a DLP 3D printer for printing to obtain a glass cylindrical sleeve preform of suitable size; the glass cylindrical sleeve preform is placed in a degreasing furnace for degreasing, cooled to room temperature, and then removed to obtain the loose porous silica cylindrical sleeve intermediate.
[0012] Furthermore, the maximum temperature of the degreasing process is 600℃-700℃.
[0013] Further, the preparation method of the loose porous silica cylindrical sleeve intermediate in step 1 is as follows: an alumina ceramic or high-purity graphite of appropriate size is used as a target rod and installed on the synchronous chuck of the OVD equipment. It is rotated and translated at a certain speed. A hydrogen-oxygen flame deposition torch is placed below the target rod, with the flame facing the target rod, and SiCl4 is introduced. After the flame hydrolysis reaction, a loose layer composed of submicron-sized spherical SiO2 particles is prepared. The target rod is translated for one stroke, and a layer of SiO2 particles is deposited. This process is repeated to obtain a loose porous silica layer of a certain thickness on the surface of the target rod. Then the target rod is removed to obtain the loose porous silica cylindrical sleeve intermediate.
[0014] Further, the preparation method of the loose porous silica cylindrical sleeve intermediate in step 1 is as follows: prepare SiO2 or its precursor sol, then pour an appropriate amount of sol into the mold for manufacturing the cylindrical sleeve to form the required cylindrical sleeve, then age the sleeve to form a cylindrical sleeve gel, and then perform degreasing treatment to obtain the loose porous silica cylindrical sleeve intermediate.
[0015] Further, the method for preparing the quartz glass cylindrical sleeve with nickel oxide micro / nano particles embedded on the surface in step 1 is as follows: a certain concentration of nickel oxide nanoparticle organic dispersion is prepared, and the degreased cylindrical sleeve blank is immersed in the nickel oxide nanoparticle organic dispersion for a certain period of time using a solution impregnation method to ensure full penetration; the impregnated cylindrical sleeve blank is placed in a vacuum furnace for sintering, and after cooling to room temperature, a quartz glass cylindrical sleeve with nickel oxide micro / nano particles embedded on the surface is obtained.
[0016] Furthermore, the nickel oxide nanoparticle organic dispersion is composed of an organic solvent and a dispersant; the organic solvent is one or more of methanol, ethanol, propanol, allyl alcohol, isopropanol, butanol, and pentanol; the dispersant is one or more of polyvinylpyrrolidone, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, gum arabic, gelatin, peach gum, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, herring oil, ammonium polyacrylate, sodium polyacrylate, sodium alginate, ammonium alginate, sodium lignosulfonate, sodium petroleum sulfonate, polyacrylamide, hydrolyzed ammonium acrylate, phosphate esters, and ethoxylated compounds.
[0017] Furthermore, the sintering conditions in the vacuum furnace are as follows: the vacuum furnace is evacuated to below 50 mbar, the sintering temperature is between 1150℃ and 1250℃, and the time is 1-2 hours.
[0018] Furthermore, the method for depositing a thin metal coating on the optical fiber surface in step 3 is specifically as follows: depositing a thin metal coating with a thickness of less than 100 micrometers on the optical fiber surface by means of chemical plating, magnetron sputtering, chemical vapor deposition, vacuum evaporation, laser-assisted maskless microdeposition, or metal fusion coating.
[0019] Further, in step 3, the metal coating includes a metal material coating and a metal composite material coating; the metal material coating is Ni, Cu, Ag, Au, Cr, NiP alloy, NiB alloy, CoB alloy, CoP alloy, NiFeP alloy, NiCoP alloy, NiCuP alloy, NiZnP alloy, NiWP alloy, NiSnP alloy, NiCuB alloy, NiFeB alloy, NiCoB alloy, NiWB alloy, NiPbB alloy, NiSnB alloy, CoWP alloy, CoFeP alloy, CoFeP alloy, CoZnP alloy, CoCuP alloy, CoSnP alloy, PdCoP alloy, and PdZnP alloy. The alloy is selected from CuSnP, NiFeCoP, NiFeZnP, NiWCuP, NiCrWP, NiSnCuP, NiCrCuP, CoNiMnP, CoFeMnP, CoWZnP, CoNiWP, CoMoWP, CoWBP, CoNiFeB, NiFeZnCuP, and CoWReBP. The metal composite material coating is a composite coating composed of the above-mentioned metal material coating and one or more micro / nano particles selected from SiC, WC, diamond, TiC, Al2O3, Cr2O3, MoS, and ZrO2.
[0020] The beneficial effects of this invention are as follows:
[0021] This invention provides a method for preparing metal-coated silica optical fibers. First, a loosely porous silica cylindrical sleeve intermediate of suitable size is prepared. After a series of processing steps, a metal thin film of less than 100 micrometers is deposited on the silica optical fiber, and then the film is thickened using electroplating technology to obtain the metal-coated silica optical fiber. This invention ensures high bonding strength between the surface of the prepared silica optical fiber and the coating layer, while preserving the mechanical properties of the optical fiber itself. Attached Figure Description
[0022] Figure 1 This is a flowchart illustrating the process of preparing a porous silica cylindrical sleeve intermediate using DLP 3D printing technology in Embodiment 1 of the present invention, and then preparing a metal-coated quartz optical fiber.
[0023] Figure 2This is a flowchart illustrating the process of preparing a porous silica cylindrical sleeve intermediate using OVD technology in Embodiment 5 of the present invention, and then preparing a metal-coated quartz optical fiber.
[0024] Figure 3 This is a flowchart illustrating the preparation of a porous silica cylindrical sleeve intermediate using sol-gel technology in Example 6 of the present invention, followed by the preparation of a metal-coated quartz optical fiber. Detailed Implementation
[0025] The present invention will now be further described with reference to the accompanying drawings.
[0026] To address the issues of high manufacturing costs and low coating thickness in current commercial optical fiber fusion coating technologies, and the shortcomings of electroplating and chemical plating techniques in preparing optical fiber metal coatings (such as insufficient coating adhesion, damage to the optical fiber itself, and inability to achieve long-distance, high-quality metallization), this invention utilizes the latest quartz glass DLP 3D printing technology, external vapor deposition (OVD), and sol-gel technology to first prepare a porous silica cylindrical sleeve intermediate of a certain size. After a series of processing steps, a metal thin film of less than 100 micrometers is deposited on the quartz optical fiber using existing chemical plating, magnetron sputtering, chemical vapor deposition, vacuum evaporation, and laser-assisted maskless micro-deposition techniques. Electroplating is then used to thicken the film, providing a new method for surface metallization of quartz optical fibers. This method ensures high bonding strength between the fiber surface and the coating layer without damaging the mechanical properties of the optical fiber itself, laying the foundation for low-cost, long-distance, and high-quality surface metallization of quartz optical fibers.
[0027] Example 1:
[0028] like Figure 1 As shown, a method for preparing a metal-coated quartz optical fiber includes the following steps:
[0029] Step 1: Prepare a loose, porous silica cylindrical sleeve intermediate of suitable size;
[0030] Using quartz glass DLP 3D printing technology:
[0031] (a) Mix the following materials evenly according to the following mass fractions: amorphous nano-quartz glass powder (approximately 50 nm, 40-50 parts), 2-hydroxyethyl methacrylate as a photopolymerization monomer (30-40 parts), 2-phenoxyethanol as a diluent (16-20 parts), tetra(ethylene glycol) diacrylate as a crosslinking agent (5-10 parts), diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as a photosensitizer (0.5-1 part), and hydroquinone as a light absorber (0.1-0.5 parts);
[0032] (b) The uniformly mixed material is placed in a DLP 3D printer for printing to obtain a glass cylindrical sleeve blank of appropriate size; then the glass cylindrical sleeve blank is placed in a degreasing furnace for degreasing, the maximum temperature of the degreasing process is 600℃-700℃, and after cooling to room temperature, it is taken out to obtain a loose and porous silica cylindrical sleeve intermediate.
[0033] Step 2: Prepare a cylindrical sleeve of quartz glass with nickel oxide micro / nano particles embedded on its surface;
[0034] (a) Prepare an organic dispersion of nickel oxide nanoparticles of a certain concentration, and immerse the loose and porous silica cylindrical sleeve intermediate in the dispersion for a certain period of time using the solution impregnation method to ensure that it is fully impregnated.
[0035] (b) The impregnated cylindrical sleeve intermediate is placed in a vacuum furnace for sintering. The vacuum furnace is evacuated to below 50 mbar, the sintering temperature is 1150℃-1250℃, and the time is 1-2 h. After cooling to room temperature, a quartz glass cylindrical sleeve with nickel oxide micro-nano particles embedded on the surface can be obtained.
[0036] Step 3: Fabricate the combination kit of cylindrical sleeve and optical fiber preform and draw the optical fiber;
[0037] The optical fiber preform is inserted into a quartz glass cylindrical sleeve with nickel oxide micro-nano particles embedded on its surface, and the preform is assembled into a kit and drawn into the desired optical fiber on a drawing tower.
[0038] Step 4: Under a hydrogen atmosphere, the drawn optical fiber is subjected to a reduction treatment to reduce the nickel oxide micro-nano particles on the surface to metallic nickel; then, a thin metal coating is deposited on the surface of the optical fiber, and then thickened by electroplating to obtain a quartz optical fiber with a certain thickness of metal coating on the surface.
[0039] Example 2:
[0040] Furthermore, the nickel oxide nanoparticle organic dispersion in Example 1 is composed of an organic solvent and a dispersant.
[0041] The organic solvent is one or more of methanol, ethanol, propanol, allyl alcohol, isopropanol, butanol, and pentanol;
[0042] The dispersant is one or more of the following: polyvinylpyrrolidone, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, gum arabic, gelatin, peach gum, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, herring oil, ammonium polyacrylate, sodium polyacrylate, sodium alginate, ammonium alginate, sodium lignosulfonate, sodium petroleum sulfonate, polyacrylamide, hydrolyzed ammonium acrylate, phosphate ester, and ethoxylated compound.
[0043] Example 3:
[0044] Furthermore, the method for depositing a thin metal coating on the surface of an optical fiber in Example 1 is as follows: a thin metal coating with a thickness of less than 100 micrometers is deposited on the surface of the optical fiber by means of chemical plating, magnetron sputtering, chemical vapor deposition, vacuum evaporation, laser-assisted maskless microdeposition, or metal fusion coating.
[0045] Example 4:
[0046] Furthermore, in Example 1, the metal coating includes a metal material coating and a metal composite material coating;
[0047] The metallic coating is one of the following: Ni, Cu, Ag, Au, Cr, NiP alloy, NiB alloy, CoB alloy, CoP alloy, NiFeP alloy, NiCoP alloy, NiCuP alloy, NiZnP alloy, NiWP alloy, NiSnP alloy, NiCuB alloy, NiFeB alloy, NiCoB alloy, NiWB alloy, NiPbB alloy, NiSnB alloy, CoWP alloy, CoFeP alloy, CoFeP alloy, CoZnP alloy, CoCuP alloy, CoSnP alloy, PdCoP alloy, PdZnP alloy, CuSnP alloy, NiFeCoP alloy, NiFeZnP alloy, NiWCuP alloy, NiCrWP alloy, NiSnCuP alloy, NiCrCuP alloy, CoNiMnP alloy, CoFeMnP alloy, CoWZnP alloy, CoNiWP alloy, CoMoWP alloy, CoWBP alloy, CoNiFeB alloy, NiFeZnCuP alloy, and CoWReBP alloy.
[0048] The metal composite coating is a composite coating composed of the above-mentioned metal material coating and one or more micro / nano particles selected from SiC, WC, diamond, TiC, Al2O3, Cr2O3, MoS, and ZrO2.
[0049] Example 5:
[0050] like Figure 2 As shown, a porous silica cylindrical sleeve intermediate is prepared using OVD technology: an alumina ceramic or high-purity graphite of appropriate size is used as a target rod and mounted on the synchronous chuck of the OVD equipment. The target rod is rotated and translated at a certain speed. A hydrogen-oxygen flame deposition torch is placed below the target rod, with the flame facing the target rod, and SiCl4 is introduced. After the flame hydrolysis reaction, a porous layer composed of submicron-sized spherical SiO2 particles is prepared. The target rod is translated once, and a layer of SiO2 particles is deposited. This process is repeated to obtain a porous silica layer of a certain thickness on the surface of the target rod. Then the target rod is removed to obtain the porous silica cylindrical sleeve intermediate.
[0051] Example 6:
[0052] like Figure 3 As shown, a loose porous silica cylindrical sleeve intermediate is obtained by using sol-gel technology: SiO2 or its precursor sol is prepared, and then an appropriate amount of sol is poured into a mold for manufacturing a cylindrical sleeve to form the required cylindrical sleeve. The sleeve is then aged to form a cylindrical sleeve gel, and then degreased to obtain a loose porous silica cylindrical sleeve intermediate.
[0053] This invention utilizes the latest quartz glass DLP 3D printing technology, external vapor deposition (OVD) technology, and sol-gel technology to first prepare a porous silica cylindrical sleeve intermediate of a certain size. After a series of processing steps, a metal thin film of less than 100 micrometers is deposited on the quartz optical fiber using existing technologies such as chemical plating, magnetron sputtering, chemical vapor deposition, vacuum evaporation, laser-assisted maskless micro-deposition, and metal fusion coating. Then, electroplating is used to thicken the film. This provides a new method for surface metallization of quartz optical fibers. This method can improve the bonding strength between the fiber surface and the coating layer without damaging the mechanical properties of the fiber body. At the same time, it lays the foundation for low-cost, long-distance, high-quality surface metallization of quartz optical fibers.
[0054] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a metal-coated quartz optical fiber, characterized in that, Includes the following steps: Step 1: Prepare a loose and porous silica cylindrical sleeve intermediate of appropriate size, and prepare a quartz glass cylindrical sleeve with nickel oxide micro and nano particles embedded on the surface. The method for preparing the quartz glass cylindrical sleeve with nickel oxide micro / nano particles embedded on the surface in step 1 is as follows: a certain concentration of nickel oxide nanoparticle organic dispersion is prepared, and a loose porous silica cylindrical sleeve intermediate is immersed in the nickel oxide nanoparticle organic dispersion for a certain period of time using a solution impregnation method to ensure full penetration; the impregnated loose porous silica cylindrical sleeve intermediate is placed in a vacuum furnace for sintering, and after cooling to room temperature, a quartz glass cylindrical sleeve with nickel oxide micro / nano particles embedded on the surface is obtained. Step 2: Insert the optical fiber preform into a quartz glass cylindrical sleeve with nickel oxide micro-nano particles embedded on its surface, assemble them into a kit, and draw them into the required optical fiber on the drawing tower; Step 3: Under a hydrogen atmosphere, the drawn optical fiber is subjected to a reduction treatment to reduce the nickel oxide micro-nano particles on the surface to metallic nickel; then, a thin metal coating is deposited on the surface of the optical fiber, and then thickened by electroplating to obtain a quartz optical fiber with a certain thickness of metal coating on the surface.
2. The method for preparing a metal-coated quartz optical fiber according to claim 1, characterized in that: The preparation method of the loose porous silica cylindrical sleeve intermediate in step 1 is as follows: 40-50 parts of amorphous nano-quartz glass powder, 30-40 parts of 2-hydroxyethyl methacrylate as a photopolymerization monomer, 16-20 parts of 2-phenoxyethanol as a diluent, 5-10 parts of tetra(ethylene glycol) diacrylate as a crosslinking agent, 0.5-1 part of diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as a photosensitizer, and 0.1-0.5 parts of hydroquinone as a light absorber are mixed evenly; the evenly mixed material is placed in a DLP 3D printer for printing to obtain a glass cylindrical sleeve preform of appropriate size; the glass cylindrical sleeve preform is placed in a degreasing furnace for degreasing, cooled to room temperature, and then removed to obtain the loose porous silica cylindrical sleeve intermediate.
3. The method for preparing a metal-coated quartz optical fiber according to claim 2, characterized in that: The maximum temperature during the degreasing process is 600℃-700℃.
4. The method for preparing a metal-coated quartz optical fiber according to claim 1, characterized in that: The preparation method of the loose porous silica cylindrical sleeve intermediate in step 1 is as follows: an alumina ceramic or high-purity graphite of appropriate size is used as a target rod and installed on the synchronous chuck of the OVD equipment. It is rotated and translated at a certain speed. A hydrogen-oxygen flame deposition torch is placed below the target rod, with the flame facing the target rod, and SiCl4 is introduced. After the flame hydrolysis reaction, a loose layer composed of submicron-sized spherical SiO2 particles is prepared. The target rod is translated for one stroke, and a layer of SiO2 particles is deposited. This process is repeated to obtain a loose porous silica layer of a certain thickness on the surface of the target rod. Then the target rod is removed to obtain the loose porous silica cylindrical sleeve intermediate.
5. The method for preparing a metal-coated quartz optical fiber according to claim 1, characterized in that: The preparation method of the loose porous silica cylindrical sleeve intermediate in step 1 is as follows: prepare SiO2 or its precursor sol, then pour an appropriate amount of sol into the mold for manufacturing the cylindrical sleeve to form the required cylindrical sleeve, then age the sleeve to form a cylindrical sleeve gel, and then perform degreasing treatment to obtain the loose porous silica cylindrical sleeve intermediate.
6. The method for preparing a metal-coated quartz optical fiber according to claim 1, characterized in that: The nickel oxide nanoparticle organic dispersion is composed of an organic solvent and a dispersant; the organic solvent is one or more of methanol, ethanol, propanol, allyl alcohol, isopropanol, butanol, and pentanol; the dispersant is one or more of polyvinylpyrrolidone, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, gum arabic, gelatin, peach gum, carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, herring oil, ammonium polyacrylate, sodium polyacrylate, sodium alginate, ammonium alginate, sodium lignosulfonate, sodium petroleum sulfonate, polyacrylamide, hydrolyzed ammonium acrylate, phosphate ester, and ethoxylated compounds.
7. The method for preparing a metal-coated quartz optical fiber according to claim 1, characterized in that: The sintering conditions in the vacuum furnace are as follows: the vacuum furnace is evacuated to below 50 mbar, the sintering temperature is between 1150℃ and 1250℃, and the time is 1-2 hours.
8. The method for preparing a metal-coated quartz optical fiber according to claim 1, characterized in that: The method for depositing a thin metal coating on the optical fiber surface in step 3 is as follows: a thin metal coating with a thickness of less than 100 micrometers is deposited on the optical fiber surface by means of chemical plating, magnetron sputtering, chemical vapor deposition, vacuum evaporation, laser-assisted maskless microdeposition, or metal fusion coating.
9. The method for preparing a metal-coated quartz optical fiber according to claim 1, characterized in that: The metal coating in step 3 includes metal material coatings and metal composite material coatings; the metal material coating is Ni, Cu, Ag, Au, Cr, NiP alloy, NiB alloy, CoB alloy, CoP alloy, NiFeP alloy, NiCoP alloy, NiCuP alloy, NiZnP alloy, NiWP alloy, NiSnP alloy, NiCuB alloy, NiFeB alloy, NiCoB alloy, NiWB alloy, NiPbB alloy, NiSnB alloy, CoWP alloy, CoFeP alloy, CoZnP alloy, CoCuP alloy, CoSnP alloy, PdCoP alloy, PdZnP alloy, CuSn The alloy is selected from the following: P alloy, NiFeCoP alloy, NiFeZnP alloy, NiWCuP alloy, NiCrWP alloy, NiSnCuP alloy, NiCrCuP alloy, CoNiMnP alloy, CoFeMnP alloy, CoWZnP alloy, CoNiWP alloy, CoMoWP alloy, CoWBP alloy, CoNiFeB alloy, NiFeZnCuP alloy, and CoWReBP alloy; the metal composite material coating is a composite coating composed of the above-mentioned metal material coating and one or more micro / nano particles selected from SiC, WC, diamond, TiC, Al2O3, Cr2O3, MoS2, and ZrO2.
Citation Information
Patent Citations
Light-guide fiber and preparation method thereof
CN109455922A
Optical fiber metal high-temperature strain sensor based on electroplating forming and preparation method of optical fiber metal high-temperature strain sensor
CN116625416A
Quartz glass with dispersed metal oxide nanoparticles and preparation method thereof
CN117142753A
Two coating high -temperature and corrosion resistance optic fibre
CN207937635U